The genome of the butternut canker pathogen, Ophiognomonia clavigignenti-juglandacearum shows an elevated number of genes associated with secondary metabolism and protection from host resistance responses - Wu, Guangxi; Schuelke, Taruna A.; Iriarte, Gloria; Broders, Kirk (PeerJ, 2020)
Ophiognomonia clavigignenti-juglandacearum (Oc-j) is a plant pathogenic fungus that causes canker and branch dieback diseases in the hardwood tree butternut, Juglans cinerea. Oc-j is a member of the order of Diaporthales, which includes many other plant pathogenic species, several of which also infect hardwood tree species. In this study, we sequenced the genome of Oc-j and achieved a high-quality assembly and delineated its phylogeny within the Diaporthales order using a genome-wide multi-gene approach. We also further examined multiple gene families that might be involved in plant pathogenicity and degradation of complex biomass, which are relevant to a pathogenic life-style in a tree host. We found that the Oc-j genome contains a greater number of genes in these gene families compared to other species in the Diaporthales. These gene families include secreted CAZymes, kinases, cytochrome P450, efflux pumps, and secondary metabolism gene clusters. The large numbers of these genes provide Oc-j with an arsenal to cope with the specific ecological niche as a pathogen of the butternut tree.
Keywords: Canker pathogen; Efflux pump; Cytochrome P450; Juglans; Fagales; Diaporthales; Pathogen evolution